2014
DOI: 10.1002/jbm.a.35294
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of primary neuronal cell proliferation using printing‐transferred carbon nanotube sheets

Abstract: Artificial nerve guidance conduits (aNGCs) prepared from polymer scaffolds and carbon nanotubes (CNTs) possess unique chemical and physical properties, and have been widely used in preclinical trials to promote neuronal differentiation and growth. However, there have been only a few reports on the clinical applicability of CNT sheets for proliferation of primary neuronal cells due to safety concerns. The present study assesses the ability and potential applicability of multiwalled CNTs (MWNTs) composited with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Our results indicate that Schwann‐like cells differentiated from ASCs are promising for treatment of peripheral nerve injuries, which is consistent with our previous study . Collectively, our findings imply that PDMS/MWNT sheets possess the ability to promote interneuronal communication, thereby indicating great potential for their application as a scaffold in peripheral nerve regeneration.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results indicate that Schwann‐like cells differentiated from ASCs are promising for treatment of peripheral nerve injuries, which is consistent with our previous study . Collectively, our findings imply that PDMS/MWNT sheets possess the ability to promote interneuronal communication, thereby indicating great potential for their application as a scaffold in peripheral nerve regeneration.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we prepared a novel scaffold for peripheral nerve regeneration, in the form of polydimethylsiloxane/multiwalled CNT (PDMS/MWNT) sheets. The biocompatibility of the PDMS/MWNT sheets for SCs was previously confirmed . Here, we characterized the biocompatibility of the PDMS/MWNT sheets for dASCs.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Chen et al showed that silicone nerve guides filled with a collagen, laminin, and fibronectin‐based gel resulted in a more mature organization of regenerating axons compared to autografts, which provided tubular support for nerve regeneration . Furthermore, Sun and coworkers prepared PDMS/multiwalled CNT sheets as an effective scaffold for peripheral nerve regeneration, which showed good biocompatibility enhanced the proliferation of neural cells and Schwan cells in vitro …”
Section: Introductionmentioning
confidence: 99%
“…In this study, a unique film of MWNT‐coated PDMS (PM) with remarkable transparency and high biocompatibility was evaluated. Transparent conduit film was prepared by controlling MWNTs density on the coating surface via a printing transfer method . To examine biocompatibility, we determined the toxicity of PM sheets against neuroblastoma cells and investigated the cell adhesive ability on the surface of PM sheets.…”
Section: Introductionmentioning
confidence: 99%